The evolution of transgender surgery. Issue 6 (20th October 2018) - Zurada, Anna; Salandy, Sonja; Roberts, Wallisa; Gielecki, Jerzy; Schober, Justine; Loukas, Marios
Abstract : An estimated 1.4% of the population worldwide has been diagnosed with Gender Dysphoria, as defined by the Diagnostic and Statistical Manual of Mental Disorders. Gender reassignment, which holistically encompasses psychotherapy, hormonal therapy and genital and nongenital surgeries, is considered the most effective treatment for transgender nonconforming patients afflicted with gender dysphoria. Little research is currently available identifying the psychosocial needs of the transgender population and their access to preventative and primary care during this transitioning process. This article presents an overview of the evolution and current approaches to genital surgical procedures available for both male‐to‐female, as well as female‐to‐male gender‐affirmation surgeries. Clin. Anat. 31:878–886, 2018. © 2018 Wiley Periodicals, Inc.